A Study on Motivational Factors and the Constraints Faced by Distance Learners of ODL Certificate Course Tea Cultivation Technology - , Bharathwaaj. A; , Balasubramaniam. P; , Sriram. N; , Nirmala Devi. M; , Gangai Selvi. R (Archives of Current Research International, 2024)
Purpose and Scope: The purpose of this study is to explore the motivational factors that influence distance learners to enrol in the ODL Certificate Course in Tea Cultivation Technology, as well as to identify the constraints they face during the learning process. The scope of this study encompasses a detailed analysis of the personal, social, economic and educational motivations of the learners, alongside the challenges related to accessibility, resources, and support systems that may hinder their learning experience. Research Design: An Ex-post facto research design was used in this research. Methodology: This study was carried out in the Nilgiris district and Coimbatore district of Tamil Nadu which is one of the major tea growing regions in India. The Tea Cultivation Technology certificate course was purposefully selected for the research because of its popularity among tea growers and its maximum enrolment. Out of 174 learners who have attended this course, 120 respondents were chosen as a sample using Simple random sampling method. A well-structured interview schedule was prepared and the data was collected using personal and telephonic interviews. Frequency and Percentage analysis followed by Garrett ranking were employed to analyse the motivational factors and the constraints of the distant learners. Results: The findings of this study revealed that the motivational factors behind the learners’ enrolment in the certificate course were determinant factors (course convenience and situational factors), job aspiration, attitude toward ODL courses and attitude toward entrepreneurship. Majority of students (69.17%) indicated a moderate level of determinant factors that affected their choice to enrol in a distance-learning certificate program. Nearly half of the Learners (45.00%) enrolled in the certificate program is for private employment. More than three-fourth of the learners (78.33%) have favourable attitude towards the ODL courses and 63.33 percent have a moderate attitude towards entrepreneurship. The research also highlights significant constraints, such as limited practical classes, monetary constraints, reduced access to resources, technological difficulties, and the struggle to balance education with other responsibilities. Conclusion: Addressing these constraints is essential for improving the overall effectiveness and accessibility of the ODL certificate course, ultimately leading to better learning outcomes and greater satisfaction among the participants in agricultural and allied sectors. Since the majority of learners had higher level of job aspiration and an entrepreneurial mindset, the provision of financial facilities to launch new businesses may serve as a motivational factor for members of the low-income group to enrol in certificate programmes.